Population status and distribution of Assamese macaques (Macaca assamensis) in Kaligandaki river basin of Baglung and Parbat districts, Nepal - Paudel, Pavan Kumar; Chalise, Mukesh Kumar (Journal of Natural History Museum, 2018)
Population status and distribution of Assamese monkey in Kaligandaki river basin was studied by direct count method and block design. Field research was conducted from November, 2015 to June, 2016.The total area of 104.70 km2 was surveyed to determine the Population status and distribution pattern of Assamese monkey. Total of 47 Assamesemacaques were counted in four different troops. The group density was found to be 0.038groups/km2 with a population density of 0.44 individuals/km2 and a mean group size of11.75 (range 3-16) individuals. Age sex composition of macaque comprised 23.40% adult males, 19.14% adult females followed by 17.02% sub adult male, 19.14% young adult female, 14.8% juveniles and 6.38% infants. Adult sex ratio was observed 1:0.81 i.e. 122males per 100 females and the recruitment rate was found 0.33. i.e. 33 infants per 100females. The distribution pattern of Assamese macaques among four different study blocks was found clumped distribution in the study area. There was significant difference in distribution of Assamese macaques among four different blocks (χ2 =6.2996 ,d.f.= 3,p= 0.09791, p>0.05).